Maternal Hepatitis B Infection Burden, Comorbidity and Pregnancy Outcome in a Low-Income Population on the Myanmar-Thailand Border: A Retrospective Cohort Study - Marieke Bierhoff; Chaisiri Angkurawaranon; Aung Myat Min; Mary Ellen Gilder; Nay Win Tun; Arunrot Keereevijitt; Aye Kyi Win; Elsi Win; Verena Ilona Carrara; Tobias Brummaier; Cindy S. Chu; Laurence Thielemans; et al. (Journal of Pregnancy)
Objectives. Hepatitis B virus (HBV) was believed to have minimal impact on pregnancy outcomes apart from the risk of perinatal transmission. In more recent years, there have been reports of adverse associations, most consistently preterm birth (PTB), but this is in the context of high rates of caesarean section. The aim of this study was to explore the association of HBV on pregnancy outcomes in marginalized, low-income populations on the Myanmar-Thailand border. Methods. HBsAg positive (+) point of care rapid detection tests results were confirmed by immunoassays. Women with a confirmed HBsAg status, HIV- and syphilis-negative at first antenatal care screening, singleton fetus and known pregnancy outcome (Aug-2012 to Dec-2016) were included. Logistic regression analysis was used to evaluate associations between HBV group (controls HBsAg negative, HBsAg+/HBeAg-, or HBsAg+/HBeAg+) and pregnancy outcome and comorbidity. Results. Most women were tested, 15,046/15,114 (99.6%) for HBV. The inclusion criteria were not met for 4,089/15,046 (27.2%) women due mainly to unavailability of pregnancy outcome and nonconfirmation of HBsAg+. In evaluable women 687/11,025 (6.2%) were HBsAg+, with 476/11,025 (4.3%) HBsAg+/HBeAg- and 211/11,025 (1.9%) were HBsAg+/HBeAg+. The caesarean section rate was low at 522/8,963 (5.8%). No significant associations were observed between pregnancy comorbidities or adverse pregnancy outcomes and HBV status. Conclusions. The results highlight the disease burden of HBV in women on the Myanmar-Thailand border and support original reports of a lack of significant associations with HBsAg+ irrespective of HBeAg status, for comorbidity, and pregnancy outcomes in deliveries supervised by skilled birth attendants.